(untitled) - CURRY, DEAN (USA, 1988)
1.Cherry blossoms / 2.Vans / 3.Navajo rug weaving / 4.Artist with courage / 5.Salt / 6.College the work - study way / 7.Alaska bush pilot / 8.New york tram / 9.Air cargo / 10.Minneapolis : a story of urban success , part I / 11.Minneapolis : a story of urban success , part II / 12.How electricity is made / 13.Rural migration / 14.Mr . colt and his six - shooter / 15.Theater for the fun of it / 16.The great american garage sale / 17.The good doctor / 18.New carrers for women / 19.Highway truckers : a special breed , part I / 20.Highway truckers : a special breed , part II
Reading and writing activities for advanced students of english as a foreing language
Keywords: INGLES